Fighting Disinformation Online: The Digital Services Act in the American Context - Daniela Peterka-Benton (Social Sciences)
The internet is one of humanity’s most significant creations in the modern era. What began roughly 30 years ago has developed into a rich, diverse, but largely unregulated environment we can no longer live without. With the spread of mis- and disinformation worldwide, calls for a safer internet have gotten louder. This article discusses the threats disinformation poses to online users and provides a case study on how the European Union’s Digital Services Act attempts to protect users’ fundamental rights in the online space and whether the Digital Services Act could or should serve as a model for similar legislation in the United States.